Assessing and nurturing character strengths among children and adolescents: overview and challenges - Oguni, Ryuji; Izumi, Tsuguyuki; Abe, Nozomi; Otake, Keiko (Frontiers in Education, 2025)
Character strengths play an important role in the healthy development of children and adolescents. However, assessing and nurturing these strengths in educational settings remain challenging. First, this review addresses the challenges of using scales to assess character strengths in children and adolescents. The currently available scales consist of many items, which makes responding to these scales burdensome for children and adolescents and leads to difficulty in using them in busy school settings. To overcome this problem, the study emphasizes the need to develop short scales that can efficiently collect data and minimize the burden on children and adolescents. Second, the review pinpoints challenges in implementing character strength interventions for children and adolescents in the said settings. We emphasize elucidating the role of interventions in the educational curriculum, thus decreasing their duration and simplifying their contents. Addressing the challenges of assessing and nurturing character strengths among children and adolescents and bridging the gap between basic research and educational practice encourage their healthy development.